(untitled) (Revista Espinhaço, 2023)
During a graduate field course, we assessed water quality, biodiversity of benthic bioindicators collected during the RAP-GANDARELA graduate course, in the Serra do Gandarela National Park, MG. This course aimed to: (a) train professionals in the use of current methodologies of Rapid Assessment Protocols (RAP) for assessment and monitoring of ecological integrity of the headwater streams; (b) contribute with baseline knowledge of aquatic biodiversity in freshwater ecosystems in the Gandarela National Park; (c) foster exchange and collaboration between master and doctoral students, park rangers, visitors, members of basin committees, ICMBio managers, stakeholders and those interested in biodiversity conservation in the Iron Quadrangle; (d) generate basic information on water quality, biodiversity of benthic macroinvertebrates that are bioindicators of water quality in the Gandarela National Park. The main results evidenced that PARNA Serra do Gandarela conserves headwater streams in reference conditions, with high diversity of physical habitats, excellent water quality, where benthic macroinvertebrates sensitive, tolerant and resistant to pollution live. Since the Gandarela National Park is responsible for the water security of most of the municipalities in the Iron Quadrangle of Minas Gerais, these streams in reference conditions must be conserved and might be used in future studies of environmental impact assessment and long-term monitoring programs of ecological conditions. Such high-grade conditions should serve as a gold standard reference for decision makers in environmental licensing processes and for projects potentially causing environmental impacts and risks to biodiversity.